Neuroprotective Effect of Ilex Paraguariensis Intake on Brain Myelin of Lung Adenocarcinoma-Bearing Male Balb/c Mice. - Cittadini, María C.; Albrecht, Claudia; Miranda, Agustín R.; Mazzuduli, Gina M.; Soria, Elio A.; Repossi, Gastón (Nutrition & Cancer, 2019)
Ilex paraguariensis (IP) is widely consumed as tea with high nutritional value. This plant contains several bioactive phenolic compounds, which are antioxidant and anti-inflammatory. On the other hand, lung adenocarcinoma (LAC) deleteriously involves neoplastic progression, inflammatory paraneoplastic syndromes, and death. Given that brain is a frequent target of this illness, our objective was to determine the neuroprotective effect of IP consumption in LAC-bearing mice. They were orally treated with 50 mg of IP extract/kg/day (IP50) for 3 weeks. Results (phenolic compounds, lipid peroxides, interleukin 6-IL-6-, tumor necrosis factor alpha -TNFα-, and luxol-stained myelination) were compared with respect to untreated controls (C) by the T test. IP50 significantly lowed brain IL-6 (2858.12 ± 57.81 pg g−1 vs. 3801.30 ± 27.34 pg g−1), whereas other variables differed in a less extent. C brains showed demyelination (low luxol-staining contrast between gray and white matters), with IP50 increasing myelination (P < 0.05). In conclusion, LAC deleterious effects on murine brain were prevented by dietary IP, which is an original discovery to develop a nutritional approach against cancer neurological compromise.